Differentiating Peromyscus leucopus bone marrow-derived macrophages for characterization of responses to Borrelia burgdorferi and lipopolysaccharide - Christopher C. Wells; Tanja Petnicki-Ocwieja; Shumin Tan; Stephen C. Bunnell; Sam R. Telford; Linden T. Hu; Jeffrey S. Bourgeois (Infection and Immunity, 2025)
ABSTRACT Currently, most tools utilized in host-pathogen interaction studies depend on the use of human or mouse (Mus musculus) cells and tissues. While these species have led to countless breakthroughs in our understanding of infectious disease, there are undoubtedly important biological processes that are missed by limiting studies to these two vertebrate species. For instance, it is well-established that a common deermouse in North America, Peromyscus leucopus, has unique interactions with microbes, which likely shape its ability to serve as a critical reservoir for numerous zoonotic pathogens, including a Lyme disease spirochete, Borrelia burgdorferi. In this work, we expand the immunological toolkit to study P. leucopus biology by performing the first differentiation of deermouse bone marrow to macrophages using P. leucopus M-CSF producing HEK293T cells. We find that P. leucopus BMDMs generated through this method behave broadly very similarly to C57BL/6J macrophages generated with the L-929 supernatant, although RNA sequencing revealed modest differences in transcriptomic responses to B. burgdorferi and lipopolysaccharide. In particular, differences in Il-10 induction and caspase expression were observed between the species.